Program Pengembangan Kewirausahaan Mahasiswa dan Alumni Di Universitas Islam Darul Ulum Lamongan - Ali Shodikin; Wahyu Kyestiati Sumarno; Sutardi Sutardi; Ali Muhajir (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
At this time, a lot of news about unemployment of higher education graduates became a special concern for the campus as the organizer. The solutions adopted include entrepreneurship education programs for students and graduates. But often entrepreneurship education programs that are carried out are not continuous and sporadic in order to obtain less optimal results. The entrepreneurship development program aims to provide entrepreneurship guidance for students and alumni of Universitas Islam Darul Ulum by prioritizing the concept of sustainable training and coaching and adjusting tenant issues. This program uses a three-phase of Participatory Action Learning System (PALS) approach, namely awareness, entrepreneurship capacity building, and institutionalization. The results were obtained that this program provided improvements in tenant management, produced science and technology-based products and formed cooperation with related parties.